Chronic cigarette smoke exposure induces microbial and inflammatory shifts and mucin changes in the murine gut. (22nd July 2015) - Allais, Liesbeth; Kerckhof, Frederiek‐Maarten; Verschuere, Stephanie; Bracke, Ken R.; De Smet, Rebecca; Laukens, Debby; Van den Abbeele, Pieter; De Vos, Martine; Boon, Nico; Brusselle, Guy G.; Cuvelier, Claude A.; Van de Wiele, Tom
Summary: Inflammatory bowel diseases (IBD) are complex multifactorial diseases characterized by an inappropriate host response to an altered commensal microbiome and dysfunctional mucus barrier. Cigarette smoking is the best known environmental risk factor in IBD. Here, we studied the influence of chronic smoke exposure on the gut microbiome, mucus layer composition and immune factors in conventional mice. We compared smoke‐exposed with air‐exposed mice ( n = 12) after a smoke exposure of 24 weeks. Both Illumina sequencing ( n = 6) and denaturing gradient gel electrophoresis ( n = 12) showed that bacterial activity and community structure were significantly altered in the colon due to smoke exposure. Interestingly, an increase of Lachnospiraceae sp. activity in the colon was observed. Also, the mRNA expression of Muc2 and Muc3 increased in the ileum, whereas Muc4 increased in the distal colon of smoke‐exposed mice ( n = 6). Furthermore, we observed increased Cxcl2 and decreased Ifn‐γ in the ileum, and increased Il‐6 and decreased Tgf‐β in the proximal colon. Tight junction gene expression remained unchanged. We infer that the modulating role of chronic smoke exposure as a latently present risk factor in the gut may be driven by the altered epithelial mucus profiles and changes in microbiome composition and immune factors.